HUBUNGAN BOBOT BADAN DAN PRODUKSI SUSU PADA KAMBING PERANAKAN ETAWA (PE) - Laya, Nibras Karnain (Jambura Journal of Animal Science, 2018)
The aim of this study was to determine how much the relationship of body weight and goat milk production of PE. This research was carried out at the Regional Technical Implementation Unit (UPTD) of Wonggahu Livestock Development in April to May 2017. The variables observed were body weight and goat milk production of PE. Number of PE goats studied by 30 tail. The data obtained were analyzed using simple regression by and simple correlation analysis by. The results showed that the average body weight of goat PE was 41.2 kg/head/day with milk production of 0.339 liter/head/day. The relationship of body weight and goat milk production of PE is strong with a correlation value of 0.691 with a coefficient of determination of 0.477. Contribution of body weight to goat milk milk production of 47.7% and the remaining 52.3% influenced by other factors not examined. the regression equation of body weight with goat milk production of PE is Y= 0,316 + 0,001 X + e.